Blocking activin receptor ligands is not sufficient to rescue cancer-associated gut microbiota - a role for gut microbial flagellin in colorectal cancer and cachexia? - Satu Pekkala; Anniina Keskitalo; Emilia Kettunen; Sanna Lensu; Noora Nykänen; Teijo Kuopio; Olli Ritvos; Jaakko Hentilä; Tuuli A. Nissinen; Juha J. Hulmi (MDPI, 2022)
Colorectal cancer (CRC) and cachexia are associated with the gut microbiota and microbial surface molecules. We characterized the CRC-associated microbiota and investigated whether cachexia affects the microbiota composition. Further, we examined the possible relationship between the microbial surface molecule flagellin and CRC. CRC cells (C26) were inoculated into mice. Activin receptor (ACVR) ligands were blocked, either before tumor formation or before and after, to increase muscle mass and prevent muscle loss. The effects of flagellin on C26-cells were studied in vitro. The occurrence of similar phenomena were studied in murine and human tumors. Cancer modulated the gut microbiota without consistent effects of blocking the ACVR ligands. However, continued treatment for muscle loss modified the association between microbiota and weight loss. Several abundant microbial taxa in cancer were flagellated. Exposure of C26-cells to flagellin increased IL6 and CCL2/MCP-1 mRNA and IL6 excretion. Murine C26 tumors expressed more IL6 and CCL2/MCP-1 mRNA than C26-cells, and human CRC tumors expressed more CCL2/MCP-1 than healthy colon sites. Additionally, flagellin decreased caspase-1 activity and the production of reactive oxygen species, and increased cytotoxicity in C26-cells. Conditioned media from flagellin-treated C26-cells deteriorated C2C12-myotubes and decreased their number. In conclusion, cancer increased flagellated microbes that may promote CRC survival and cachexia by inducing inflammatory proteins such as MCP-1. Cancer-associated gut microbiota could not be rescued by blocking ACVR ligands.